Impact of R-loops on oncogene-induced replication stress in cancer cells - Heuzé, Jonathan; Lin, Yea-Lih; Lengronne, Armelle; Poli, Jérôme; Pasero, Philippe (Comptes Rendus Biologies)
Replication stress is an alteration in the progression of replication forks caused by a variety of events of endogenous or exogenous origin. In precancerous lesions, this stress is exacerbated by the deregulation of oncogenic pathways, which notably disrupts the coordination between replication and transcription, and leads to genetic instability and cancer development. It is now well established that transcription can interfere with genome replication in different ways, such as head-on collisions between polymerases, accumulation of positive DNA supercoils or formation of R-loops. These structures form during transcription when nascent RNA reanneals with DNA behind the RNA polymerase, forming a stable DNA:RNA hybrid. In this review, we discuss how these different cotranscriptional processes disrupt the progression of replication forks and how they contribute to genetic instability in cancer cells.